A semi-virtual two dimensional gel electrophoresis: IF–ESI LC-MS/MS - Stanislav Naryzhny; Victor Zgoda; Artur Kopylov; Elena Petrenko; Аlexander Archakov (MethodsX, 2017)
A method for increasing the productivity of ESI LC-MS/MS (electrospray ionization-liquid chromatography-tandem mass spectrometry) was proposed and applied. After IF (isoelectric focusing) of the sample using IPG (immobilized pH gradient) strip, the strip was cut to sections, and every section was treated according to trypsinolysis protocol for MS/MS analysis. The peptides produced were further analyzed by ESI LC-MS/MS. The procedure allows to: • identify many more proteins and proteoforms compared to shotgun analysis of extracts. • build a semi-virtual 2DE map of identified proteins.